Five new species of Culicoides Latreille described from Colombia, yielding a new species list and country records (Diptera: Ceratopogonidae) - Spinelli, Gustavo Ricardo (2009)
The following five new species of Culicoides from Colombia are described, illustrated and placed to subgenus or species group: Culicoides antioquiensis, Culicoides gabrieli, Culicoides inermis, Culicoides micayensis and Culicoides nigrifemur. C. gabrieli is also known from Peru. When possible, their position in previously published keys is indicated and their features discussed in light of the most recent revisions. A list of 180 Culicoides species known (114) or suspected of being in Colombia (66) is given in a Table. Of these, 12 including the new species are recorded from Colombia for the first time.